2016
DOI: 10.23917/jramathedu.v1i1.1783
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fractional Cards for Fraction Learning in The Fifth Grade Students of Elementary School

Abstract: This research aims to investigate the use of fractional cards on teaching in the fifth grade students of Elementary School. The method used is descriptive qualitative. The researcher used observation, interview, and documentation to collect the data. The results showed that there was an increase on the students' enthusiasm for learning process, and there were 27 students (69.23%) that have a score above the Minimum Criteria of Mastery (Kriteria Ketuntasan Minimal/KKM). The study concludes that the use of fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…So when performing simple addition and subtraction operations, the result can be checked immediately using teaching aids. In line with the results of Indriani's (2016) research which showed that the use of fractional cards can help the learning process in fractional material. According to the study, the use of teaching aids in this study, students can see first-hand the concepts of fractions and angles that are demonstrated.…”
Section: Resultssupporting
confidence: 84%
“…So when performing simple addition and subtraction operations, the result can be checked immediately using teaching aids. In line with the results of Indriani's (2016) research which showed that the use of fractional cards can help the learning process in fractional material. According to the study, the use of teaching aids in this study, students can see first-hand the concepts of fractions and angles that are demonstrated.…”
Section: Resultssupporting
confidence: 84%
“…Seorang guru matematika yang mumpuni dalam pemahaman terhadap perkembangan anak, akan dapat mengusahakan agar pebelajaran yang disampaikan sesuai dengan fakta, konsep, operasi, dan juga sesuai dengan prinsip dalam matematika, sehingga apa yang disampaikan dalam pembelajaran matematika sangat dapat dipahami secara konkrit (Sudarman, 2011). Terkait dengan teori kognitif Piaget dalam cara berpikir siswa sekolah dasar berada pada fase pemikiran operasional konkrit (Indriani, 2016) (Wiryanto, 2020) (Fahma & Purwaningrum, 2021) (Nabila, 2021) (Hidayati, 2012), yaitu fase yang mengfokuskan anak pada kemampuan mental anak yang dapat mejadikan objek menjadi konkrit atau pada peristiwa yang pernah dialaminya. Proses pembelajaran utamanya matematika di Pendidikan Dasar (SD) dapat dilakukan dalam bentuk pendidikan yang menitikberatkan pada peletakan landasan menuju pertumbuhan dan perkembangan jasmani dan rohani yang meliputi pada kemampuan daya pikir, kreativitas, kecerdasan emosional, dan cerdas dalam hal spiritual), sosio emosional, bahasa dan komunikasi (Bayujaga & Mariani, 2020).…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan apa yang dikemukakan oleh (Indriani, 2016); (Anggoro, 2019); (Perminov, Anakhov, Grishin, & Savitskiy, 2016) bahwa pembelajaran matematika hendaknya menggunakan media bantu seperti alat peraga, sehingga siswa mampu memahami konsep yang abstrak menjadi lebih konkrit. Hal ini sesuai dengan pembelajaran yang berorientasi PAIKEM, dimana siswa aktif dalam pembelajaran, mampu memberikan ide kreatif, sehingga tujuan pembelajaran tercapai dan pembelajaran yang berlangsung menarik dan menyenangkan (Moyer-Packenham, 2012); (Michels, O'Gorman, & Ruth Kucian, 2018); .…”
Section: Evaluasi Pembelajaran Paikemunclassified